Analysis of Genetic Variability and Heritability of Agronomic Characters from Crossing Yardlong Bean of Fagiola IPB x Super Putih - Bakhtiar, Ikrima Farishani; Anwar, Syaiful; Kusmiyati, Florentina (Universitas Muhammadiyah Malang, 2020)
This research aim was to estimate the variability value and heritability of quantitative and qualitative character on F4 generation from crossing Fagiola IPB and Super Putih. The observed parameters were plant height, number of leaves, number of branches, the day of flowering, length of young pod, pod color, number of pod, number of seeds, seed weight, weight of one seed, weight of 100 seeds, and sweetness. Data were analized by Analysis of Variance, Genetic Variability, and Heritability. The result showed that only character of seed weight per plant had high genetic variability. The characters of number of leaves, number of branches, length of young pods, number of old pods, number of seeds, weight of seeds, one seed weight, and weight of 100 seeds had high heritability. The day of flowering and sweetness had low heritability. The results of the dendogram analysis showed that group C was recommended for next generations.